Increase and Decrease in Toxoplasmosis Infected Birth Rate from the Sensitivity Analysis - Meri Hari Yanni; Teuku Afriliansyah; Sulasri Suddin (Universitas Muhammadiyah Mataram, 2021)
This article aims to look at the dynamics of the toxoplasmosis epidemic with the effect of vaccination by increasing and decreasing the birth rate of infected with toxoplasmosis. The method used in this research is literature study and continued by using numerical simulation analysis. The research procedure used in this study is to simulate and analyze the parameters that affect the population. Some of the data used are secondary data on toxoplasmosis sufferers obtained from the Banda Aceh Health Office in 2018. From the numerical simulation results of the toxoplasmosis epidemic model with the vaccination effect, it was found that when the birth rate was infected with toxoplasmosis increased by at 5% then the number of individuals infected with toxoplasmosis, controlled individuals and the number of vaccinated individuals increases with the basic reproductive number Ro > 1. In this condition, there are no individuals who are susceptible to toxoplasmosis again so that vaccination for susceptible individuals can quickly overcome the spread of toxoplasmosis. Furthermore, the rate of births infected with toxoplasmosis decreases of 5% is obtained search population in the toxoplasmosis epidemic model has decreased with the basic reproduction number Ro <1. In this condition, the number of individuals in each population has decreased, resulting in the spread of toxoplasmosis disappeared from the population. So that this research can contribute to health science and the government in overcoming the toxoplasmosis epidemic.